THE IMPACT OF CEO POWER ON STOCK PRICE CRASH RISK IN FAMILY BUSINESSES: EVIDENCE FROM INDONESIA - Sukiantono Tang; Sheila Septiany; Budi Harsono; Serly Serly; Ilena Nurpavitia (Faculty of Economics and Business, 2026)
This study analyzes the effect of Chief Executive Officer (CEO) power and non-family CEO status on stock price crash risk in family-owned firms in Indonesia. The study is motivated by agency theory, which emphasizes potential conflicts arising from concentrated managerial power that may harm shareholder interests and capital market stability. A quantitative approach is employed using panel data from 75 family firms listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, resulting in 226 firm-year observations. Panel data regression analysis is conducted using STATA to examine the effects of non-family CEO status, CEO power, and their interaction on stock price crash risk. The results show that the presence of a non-family CEO has a negative and significant effect on stock price crash risk, indicating that professional management can reduce information asymmetry. CEO power, when analyzed independently, also exhibits a significant negative effect on crash risk. However, the interaction between non-family CEO status and high CEO power significantly increases stock price crash risk, suggesting opportunistic behavior under weak governance structures. This study concludes that professional leadership must be accompanied by strong corporate governance mechanisms to mitigate financial risk in family-owned firms. The findings provide implications for investors and policymakers.